62.5k views
0 votes
Which is a solution for this equation? Log base 2 x = 2 - log base 2 (x - 3)

X = 1
X = 2
X = 3
X = 4
X = 5

1 Answer

3 votes

Answer: Fourth Option


x =4

Explanation:

First we write the equation


log_2(x) = 2- log_2(x-3)

Now we use the properties of logarithms to simplify the expression


log_2(x)+log_2(x-3) = 2

The property of the sum of logarithms says that:


log_a (B) + log_a (D) = log_a (B * D)

Then


log_2[x(x-3)]= 2

Now use the property of the inverse of the logarithms


a ^ {log_a (x)} = x


2^(log_2[(x)(x-3)])= 2^2


(x)(x-3))}= 4


x^2-3x -4=0


x^2-3x -4=(x-4)(x+1)=0

Then the solution are


x= -1 and
x= 4

We take the positive solution because the logarithm of a negative number does not exist

Finally the solution is:


x =4

User IrkenInvader
by
5.6k points